New Wine in Old Bottles - Wriston, Walter B. (Tufts Archival Research Center, 2008)
The document was created from the speech, "New Wine in Old Bottles," written by Walter B. Wriston for the Indiana University School of Business on 18 April 1989. The original speech is located in MS134.001.009.00010.